A TCAD study on the effect of process parameters on silicon optical phase shifter performance - Mishra, Darpan; Sonkar, Ramesh Kumar (Frontiers in Physics, 2023)
On-chip integrated optical phase shifters are an important part of optical phase modulators. The performance of such modulators relies heavily on the phase shifter performance, which in turn depends on multiple process parameters. This paper reports the study of the effect of different process parameters on the performance of a silicon PN optical phase shifter obtained by process simulation using Silvaco® TCAD. The effect of dopant implantation dose, implantation energy, annealing temperature and time, wafer temperature, wafer tilt and rotation, and pre-amorphization on the phase and absorption of light is discussed. The 3-dB modulation bandwidth of a lumped phase shifter and the dependency of the performance metrics on different process parameters are presented. Monte Carlo numerical simulation shows that the free-carrier absorption has a much greater dependency on the process parameters than the phase shift. The study shows that ion channeling poses a limiting factor on the phase shifter performance, which can be improved by tilting the wafer or using a pre-amorphized substrate for implantation. The study shows that the 3-dB modulation bandwidth is highly dependent on the wafer tilt angle, rotation angle, and the lattice structure of the solid substrate. A bandwidth improvement of more than 5× is observed with 1.7× lower absorption for a pre-amorphized sample at -5 V compared to a crystalline sample with the same process flow.